Analisis Campuran Aspal Porus dengan Penambahan Filler Mill Scale Limbah Besi Baja - Gavrela, Iqbal Hayes; Hartatik, Nurani; Rizkiardi, Aditya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Porous asphalt emerges as an innovation in flexible pavement that allows water to flow vertically and horizontally into the base layer, while also providing skid resistance, reducing the risk of aquaplaning, and minimizing traffic noise. This study uses 60/70 penetration asphalt as a binder and investigates the addition of mill scale steel waste as a filler in porous asphalt mixtures. Mill scale is a by-product of the steel industry in the form of metal oxide, formed through the hot-rolled process at temperatures of 700–900 °C. The utilization of this waste as a filler is considered strategically valuable as it can reduce environmental pollution while supporting the principles of sustainable development. The purpose of this study is to analyze the characteristics of porous asphalt mixtures with the addition of mill scale filler from steel waste, in order to determine the mixture's performance and its potential application in road infrastructure in Indonesia.